Kewenangan Mengadili Tindakan Faktual oleh Pejabat (Perbuatan Melawan Hukum) Melalui Citizen Lawsuit : Studi Kasus Putusan Nomor 756/PDT.G/2020/PN.MDN - Maulidya Shamira Putri Prabowo (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to determine the distinction in jurisdiction between the District Court and the State Administrative Court in adjudicating lawsuit cases against public officials arising from factual actions and the non-issuance of State Administrative Decisions, and to ascertain the authority of the District Court in adjudicating disputes concerning factual actions and the refusal to issue State Adminstrative Decisions through citizen lawsuit. This study employs a normative legal research methodology with a case study approach. The types of legal materials used are primary and secondary legal materials. The data collection technique utilized is literature review. The legal material analysis technique in this research employs deductive syllogism. The findings of this research indicate that the difference in jurisdiction between the District Court and the State Administrative Court in adjudicating lawsuit cases against public officials due to the non-issuance of State Administrative Decisions lies in the nature of the State Administrative Decision itself. The District Court has the authority to adjudicate disputes related to factual actions and disputes concerning State Administrative Decisions, provided that the lawsuit is filed through a citizen lawsuit.